ANALISA MACAM DOSIS KOTORAN CACING DAN SISTEM JAJAR LEGOWO PADA HASIL TANAMAN PADI (Oryza sativa L) - Ita Ery Etika Wati; Choirul Anam; Mutiara Kusumaningtyas Pitaloka (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2022)
Rice (Oryza sativa L.) is a very important cultivated plant for the people because more than half of the world's population depends on this plant as a main source of food. Organic rice cultivation systems and spacing systems need to be considered because the excessive use of chemical fertilizers causes the low ability of the soil to absorb water. In addition, the lack of education on the best spacing pattern causes a decrease in rice production.This research aims to determine the effect of the jajar legowo system on the treatment of the jajar legowo system and the dose of worm manure fertilizer on the growth and production of rice plant. This study used a factorial Randomized Block Design (RAK) method, which consisted of 2 factors, namely the worm manure fertilizer and the legowo row system. The best legowo line system is 2:1. In this treatment all parameters show high results. The best combination in all treatments was 9 t/ha of vermicompost and 2:1 spacing of jajar legowo.